Analisis Kepuasan Pengguna E-Learning Menggunakan System Usability Scale (SUS) (Studi Kasus : MA Muhammadiyah 1 Malang) - Naufal Adiftya Falah; Evi Dwi Wahyuni; Vinna Rahmayanti Setyaning Nastiti (Jurnal Repositor, 2023)
The corona virus is sweeping the globe, leaving a massive amount of activity outside of the room paralyzed, especially educational activities such as school and college. With the plague, e-learning was one alternative to the institution of education for online media studies, it was no exception for MA Muhammadiyah 1 Malang City. The MA Muhammadiyah 1 Malang City has been using e-learning since its 2019/2020 year, but no test has ever been made of its user satisfaction. So the purpose of this study was to find out the extent of the unfortunate success and satisfaction of the user e-learning MA Muhammadiyah 1 Malang City. In conducting study a valued instrument can measure the user satisfaction analysis using the usability scale system (SUS). For the respondents in this study are all the active teachers and the MA Muhammadiyah 1 Malang City students with a total of 125. The results of these tests scored an average score - the average SUS for teachers by 73, x class by 77, xi class by 75 and xii by 74. From the average result, the grade scale c and the variant, with so MA Muhammadiyah 1 Malang City e-learning ma can be declared worthy and acceptable by its user.